Unrivaled : a novel - Mitchell, Siri L., 1969- (Bethany House, 2013)
"Lucy Kendall always assumed she'd help her father in his candy-making business, creating recipes and aiding him in their shared passion. But after a year traveling in Europe, Lucy returns to 1910 St. Louis to find her father unwell and her mother planning to sell the struggling candy company. Determined to help, Lucy vows to create a candy that will reverse their fortunes. St. Louis newcomer Charlie Clarke is determined to help his father dominate the nation's candy industry. Compromise is not an option when the prize is a father's approval, and falling in love with a business rival is a recipe for disaster when only one company can win. Will these two star-crossed lovers let a competition that turns less than friendly sour their dreams?"--Amazon.com, viewed February 27, 2013.